Psychological determinants of economics. Critical analysis of common areas of research in economics and psychology - Wojciechowska, Renata (Psychologiczne uwarunkowania ekonomii. Analiza krytyczna wspólnych obszarów badawczych ekonomii i psychologii, 2018)
Economics needs psychology. It is impossible to explain social and economic phenomena on the basis of typical economic models. Economics has opened to social sciences and thus modified its own test methods and language, and extended the research area. As a result of the cooperation between economics and psychology, numerous scientific subdisciplines were formed, and economic models and theories developed new meanings and applications. Yet, not every interdisciplinary research is cognitively fertile for economics. What economics risks is losing its own scientific identity and sight of its subject of research. The purpose of the paper is to analyse the opportunities and threats that appear in the scope of research done and actions taken in economics and psychology
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 529; s. 393-401
Keywords: economic psychology; experimental economics; behavioural economics; test method; psychology; economics; psychologia ekonomiczna; ekonomia eksperymentalna; ekonomia behawioralna; metoda badawcza; psychologia; ekonomia